The Influence of Profitability, Firm Dynamics, and Digital Transformation on Firm Value - Hendri Mustaqim; Zuraida Zuraida; Fifi Yusmita (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2025)
This research aims to analyze both the simultaneous and individual impacts of profitability, firm dynamics, and digital transformation on firm value. A causal research design is utilized in this study. The population consists of mining companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2022. A purposive sampling method was applied, selecting mining companies that met specific criteria, resulting in a total of 200 observations. The study uses secondary data sources, and the analytical method employed is panel data regression. The findings reveal that profitability, firm dynamics, and digital transformation collectively have a significant influence on firm value. Individually, profitability shows a negative relationship with firm value, while firm dynamics exhibit a positive impact.